A Flexible Oxygenated Carbographite Nanofilamentous Buckypaper as an Amphiphilic Membrane. Issue 8 (8th March 2018) - Homaeigohar, Shahin; Strunskus, Thomas; Strobel, Julian; Kienle, Lorenz; Elbahri, Mady
Abstract: Here, for the first time, oxygenated amorphous carbon/graphite (a‐CO x /G) hybrid nanofilaments are produced and used as the building blocks of a buckypaper membrane. The nanofilaments are in fact the innovatively chopped version of brittle, highly graphitized polyacrylonitrile precursor nanofibers. The high temperature (1250 °C) graphitization and then fast cooling bring about biphasic nanofibers made of graphite and amorphous carbon, readily reoxidized during cooling. The combination of polar and nonpolar domains in the nanofilaments governs a desirable amphiphilicity, thus selectivity to a variety of polar/nonpolar water pollutants. Through electrostatic and π–π interactions, the membrane efficiently discriminates amphiphilic castor oil as well as cationic methylene blue dye from water. Moreover, the buckypaper‐like structure of the membrane is 100% efficient in depth filtration of colloidal particles from water. The membrane's water flux is 16 times higher than that of commercial microfiltration membranes, promising an advanced energy/cost efficient filtration process. Thus, being multispectrally selective and highly water permeable, the a‐CO x /G nanofilamentous membrane is regarded potentially a next‐generation, cost‐effective, and sustainable alternative to the long‐existing thin‐film composite membranes for water treatment. Abstract : Graphite nanomaterials are superhydrophobic and selectively adsorb nonpolar water pollutants. Yet, this feature hinders their applicability in dynamic membrane processes due to fouling and presence of polar pollutants, unless they are hydrophilized. Here, graphite nanofilaments as the building blocks of a buckypaper membrane are oxidized (hydrophilized) through a customized thermal treatment to be able to remove polar and nonpolar pollutants.